ANALISIS KINERJA KEUANGAN TERHADAP BELANJA MODAL DALAM LAPORAN REALISASI ANGGARAN PEMERINTAH DAERAH (STUDI KASUS PADA KAB/KOTA SE-JAWA TIMUR 2020-2021) - Yunita Wulandari, Sheriyana (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to find out how much influence the PAD growth rate, independece level, effectiveness level, efficiency level on capital expenditures partially and simultaneously has on the district or city budget realization reports in East Java from 2020 to 2021. This study uses a quantitative descriptive method with data analysis techniques using panel data regression analysis and assisted by STATA for windows version 16. The results of this study indicate that the growth rate of PAD and level of efficiency partially have a significant effect on capital expenditure. While the level of independece and the level of effectiveness have no significant effect on capital expenditures. Simultaneously the growth rate of PAD, independence, effectiveness, and efficiency have a significant effect on capital expenditures. This research has data novelty in the form of a year period, namely 2020-2021 and supporting software, namely STATA for windows version 16.